Automation: programmable controller / Azmi Abdul Hamid and Samsuddin Awang - Abdul Hamid, Azmi; Awang, Samsuddin (1986)
The development of microprocessor introduces Programmable Controller as a substitute for the electro-mechanical relay logic automation system. Most industrial processes require several operations to produce the required output. Thus, small size, reliable, flexible, simple programming and low cost programmable controller (PC) are used. The design of PC is based on the MC 6802 GPU which performs the scanning of the inputs and traverses the stored program in the EPROM and/or RAM line by line and logically or arithmetically combines the inputs and outputs as specified by the program and determine the appropriate output. The programmer consists of several special function keys where ladder diagram and mnemonic programming language is used to program the PC. The I/0 module provide the link between the controller and the process equipment/device to be controlled. The input interface provides the isolation between the equipment which includes pushbutton, limit swiches, sensors and optocoupler as an input conditioners and convert the input signal to a form acceptable to the controller. The output interface convert PC signal to a form which can be used by the process equipment through optocouplers.